Archlog: High-level synthesis of reconfigurable multiprocessors for logic programming - Fidjeland,A; Luk,W (2006)
This paper presents Archlog, a language and framework for designing multiprocessor architectures in the logic programming domain. Our goal is to enable application developers in areas such as machine learning and cognitive robotics to produce high-performance designs for reconfigurable devices, without detailed knowledge of hardware development. The Archlog framework provides a high level of abstraction, enabling rapid system generation while supporting high performance. In this paper we present the Archlog language and its library-based compilation framework, which makes use of a customisable logic programming processor. The system generates multiple designs, with different trade-offs in the use of reconfigurable logic and embedded memories. An implementation of a multiprocessor for the machine learning system Progol on a 40MHz XC2V6000 FPGA is 10 times faster than a 2GHz Pentium 4 processor. © 2006 IEEE.